1996
DOI: 10.1016/s1198-743x(15)60284-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chlamydia trachomatis, Chlamydia psittaci and Chlamydia pneumoniae antibodies in blood donors and attendees of STD clinics

Abstract: OBJECTIVE: To estimate the prevalence of Chlamydia trachomatis, C. psittaci and C. pneumoniae antibodies in sera from altogether 931 blood donors, patients with symptoms of urethritis, assumed salpingitis and sexually acquired reactive arthritis (SARA), and women with fertility problems. METHODS: IgG antibodies to C. trachomatis, C. psittaci and C. pneumoniae were determined by microimmunofluorescence (MIF) tests. All patients were also tested for genital C. trachomatis infection using direct immunofluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The test detects both group-specific lipopolysaccharide and species-specific antibodies [13]. Therefore, women with a positive serology but with a normal pelvis may have cross-reactive responses to past infection with other species of chlamydia such as Chlamydia pneumoniae [14] or Chlamydia psittaci [12,15]. In our study we did not evaluate C. pneumoniae antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The test detects both group-specific lipopolysaccharide and species-specific antibodies [13]. Therefore, women with a positive serology but with a normal pelvis may have cross-reactive responses to past infection with other species of chlamydia such as Chlamydia pneumoniae [14] or Chlamydia psittaci [12,15]. In our study we did not evaluate C. pneumoniae antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Sera from patients exposed to C. trachomatis show diverse serological profiles against immunodominant C. trachomatis antigens (2,18,42,47,49), many of which are cross-reactive with sera from patients exposed to other chlamydial species, in particular C. pneumoniae (2,5,19,44). In addition, C. trachomatis antigens, such as the 60-kDa heat shock protein (hsp60) and lipopolysaccharide (LPS), cross-react with other bacterial species (35,50,57).…”
mentioning
confidence: 99%
“…Microimmunofluorescence (MIF) (54), which detects antibodies to chlamydial elementary bodies (EB), has long been considered the "gold standard" for the serodiagnosis of chlamydial infections (55). However, the procedure lacks standardization and is subjective; moreover, its specificity is considered suspect because of cross-reactivity with other chlamydial species (5,27,40,44). A number of ELISAs are also commercially available, including several based on peptides of MOMP, which makes up 60% of the total outer membrane protein and is highly immunogenic (8).…”
mentioning
confidence: 99%
“…Thirty‐nine serum samples from patients with diagnosed SARA were selected on the basis of the results of the MIF test [18], i.e. meeting requirements for groups 1 and 2 (see below).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study [18]we found that antibody reactivity to all three chlamydial species occurred more often in patients with urethritis, assumed salpingitis, fertility problems and sexually acquired reactive arthritis (SARA) than in blood donors. This was also true for those who were direct immunofluorescence (DIF)‐positive, but not for those in whom no elementary bodies (EBs) were found.…”
Section: Introductionmentioning
confidence: 96%